PENGARUH PENAMBAHAN BUAH-BUAHAN DALAM PAKAN TERHADAP PERUBAHAN WARNA RAMBUT PADA OPOSUM LAYANG (PETAURUS BREVICEPS) JENIS CLASSIC GRAY - Farida, Wartika Rosa; Sari, Andri Permata; Handayani, Tri Hadi; Inayah, Nurul; Nugroho, Herjuno Ari (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTThis study aims to determine the possibility of changes in the hair color on young sugar gliders (Petaurus breviceps) were given additional fruits in the feed. Research has been conducted in the Small Mammal Captive Breeding of Zoology Division, Research Center for Biology - LIPI, Cibinong, Bogor. Descriptive method used in this study with 10 days of preliminary and 90 days (3 months) of data collection period. The research material used is 16 young sugar gliders aged about 2-3 months, divided into 2 groups namely group I consists of 8 sugar gliders (4 male and 4 female) whose the parent is brownish brown color, while group II consists of 8 sugar gliders (4 male and 4 females) whose the parent are gray in color. Each group received 2 feeding porridge formulations T0 (control) and T1 (T0 + kepok banana (Musa balbisiana), watermelon (Citrullus lanatus), and red dragon fruit (Hylocereus polyrhizus)). T0 feed composition consists of brown rice porridge, boiled chicken eggs, honey, calcium, and water. Sugar gliders is given live superworm (Zophobas morio) every Tuesday and every Thursday is given live crickets (Gryllidae). During the observation each pair  of young sugar glider is placed in a wire enclosure (60 cm x 42 cm x 42 cm) equipped with feeding box, drinking water bottle and a hammock. The results showed that the average of dry matter intake T1> T0. KII / T0 / enclosure 6 show higher of body weight gain and feed efficiency than KI / T1 / enclosure 4. The addition of fruits into the T1 diet did not show any discoloration in hair on sugar gliders in captivity.  Keywords: fruits, feed intake, hair/fur color, Petaurus breviceps